In the wings - Goldman, Katie (New York Dial Press, 1982)
Playing one of the leading roles in her school's production of "The Prime of Miss Jean Brodie" helps Jessie forget about the increasing rift between her parents.
Keywords: Theater -- Fiction; Divorce -- Fiction; Schools -- Fiction